DEVELOPMENT OF CREATIVE ECONOMY BASED BUSINESS IN BALI PROVINCE - Imsar; Purnama Ramadani Silalahi; Ahmad Muhaisin B Syarbaini (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2025)
This multisite study aims to identify common patterns and develop new propositions and theories based on research conducted at two locations: The Keranjang Bali and Krisna Oleh-Oleh Bali. Using a qualitative approach with a case study and multisite design, this study collects primary data through interviews and observations, while secondary data is obtained from documentation. Data analysis is conducted using both single-site and cross-site methods. The findings reveal differences in income enhancement strategies between the two businesses within the context of creative economy-based MSME. The Keranjang Bali provides employees with opportunities to increase their income by channeling their creativity, supported by capital from business owners, one example being the Solar Tees t-shirt product. To overcome obstacles in MSME development, both businesses enhance human resource skills by providing training to prospective employees before they become permanent staff. Additionally, the Department of Cooperatives and MSME plays a crucial role in supporting business development within the community. The expected outcome of this research is to offer effective strategies for improving employee and business owner income by positioning employees and the community as agents of change, driving innovation in creative economy-based MSME.